Sustained immunotolerance in multiple sclerosis after stem cell transplant. Issue 2 (1st February 2022) - Visweswaran, Malini; Hendrawan, Kevin; Massey, Jennifer C.; Khoo, Melissa L.; Ford, Carole D.; Zaunders, John J.; Withers, Barbara; Sutton, Ian J.; Ma, David D. F.; Moore, John J.
Abstract: Objective: Autologous haematopoietic stem cell transplantation (AHSCT) has the potential to induce sustained periods of disease remission in multiple sclerosis (MS), which is an inflammatory disease of the central nervous system (CNS) characterised by demyelination and axonal degeneration. However, the mechanisms associated with durable treatment responses in MS require further elucidation. Methods: To characterise the longer term immune reconstitution effects of AHSCT at 24 and 36 months (M) post‐transplant, high‐dimensional immunophenotyping of peripheral blood mononuclear cells from 22 MS patients was performed using two custom‐designed 18‐colour flow cytometry panels. Results: The higher baseline frequencies of specific pro‐inflammatory immune cells (T‐helper‐17 (Th17) cells, mucosal‐associated invariant T‐cells and CNS‐homing T‐conventional (T‐conv) cells observed in MS patients were decreased post‐AHSCT by 36M. This was accompanied by a post‐AHSCT increase in frequencies and absolute counts of immunoregulatory CD56 hi natural killer cells at 24M and terminally differentiated CD8 + CD28 − CD57 + cells until 36M. A sustained increase in the proportion of naïve B‐cells, with persistent depletion of memory B‐cells and plasmablasts was observed until 36M. Reconstitution of the B‐cell repertoire was accompanied by a reduction in the frequency of circulating T‐follicular helper cells (cTfh) expressing programmed cell death‐1 (PD1 + ) at 36M. Associations between frequency dynamics and clinical outcomes indicated only responder patients to exhibit a decrease in Th17, CNS‐homing T‐conv and PD1 + cTfh pro‐inflammatory subsets at 36M, and an increase in CD39 + T‐regulatory cells at 24M. Interpretation: AHSCT induces substantial recalibration of pro‐inflammatory and immunoregulatory components of the immune system of MS patients for up to 36M post‐transplant.